Fracture-dislocations of the proximal ulna - Gereli, Arel; Nalbantoglu, Ufuk; Dikmen, Goksel; Seyhan, Mustafa; Turkmen, Metin (TURKISH ASSOC ORTHOPAEDICS TRAUMATOLOGY, 2015)
Objective: To investigate the relationship between injury patterns, complications, and the functional outcomes of patients with proximal-ulna fracture-dislocations. Methods: Retrospective analysis of 15 patients (10 men, 5 women

mean age, 49.1 years

mean follow-up 49 months) with 6 anterior and 9 posterior fracture-dislocations of the proximal ulna. The proximal ulna was reconstructed with plates and screws in 13 patients and tension-band wiring in 2 patients. At the final follow-up, elbow range of motion (ROM) was measured and Mayo elbow scores (MEPS) were recorded. Broberg-Morrey criteria were used for osteoarthritis staging. Results: Concomitant radial-head fracture was seen in all posterior fracture-dislocations. Four ligamentous injuries occurred in this group. All anterior dislocations had trochlear-notch fractures without associated injuries. Mean flexion ROM was 130.6 degrees (100 degrees-140 degrees) and mean loss of extension ROM was 12.6 degrees (0 degrees-30 degrees) in the study group. The mean MEPS score was 92.3 (70-100). Patients with posterior fracture-dislocations showed lower ROM and MEPS and higher level of osteoarthritis than patients with anterior fracture-dislocations. Recurrent dislocations occurred in 2 patients who had ulna fractures fixed with tension-band wiring. Conclusion: Radial-head fracture and ligamentous injury are specific components of posterior fracture-dislocations. The injury is limited to the trochlear notch in anterior fracture-dislocations. Posterior fracture-dislocations have lower functional outcomes. Proximal-ulna fractures should be fixed with rigid internal fixation (plate and screw) even if the fracture is a simple 2-part fracture.
Keywords: Proximal ulna; elbow dislocation; fracture-dislocation